South American rice water weevil, Oryzophagus oryzae, and other water weevils population dynamics in irrigated rice - Hickel, Eduardo Rodrigues (Revista de Ciências Agroveterinárias, 2013)
The South American rice water weevil, Oryzophagus oryzae (Costa Lima) (Coleoptera: Curculionidae), and other water weevils population dynamics in irrigated rice fields in Santa Catarina State, Brasil, is still unknown. This makes the development and practice of new strategies of integrated pest management difficult as well as the timing of insecticide application for pest control. The aim of this study was monitoring the water weevils population to know their population dynamics and their periods of movement in the irrigated rice fields. Three light traps, model “Luiz de Queiroz”, were set in an irrigated rice field at Epagri Experimental Station, in Itajaí, SC. From October 2007 to April 2012 the light traps were turned on, from 4 pm to 9 am once a week, except from May to August of each year when a fortnight schedule was followed. O. oryzae and other water weevils move with more intensity from the hibernation sites to rice fields in October and leave the rice fields to for hibernation sites between January and first days of March.